Sacred Sites, Rituals, and Performances New Perspective for Religious Tourism Development - Shinde, Kiran (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The conceptual territory of religious tourism is fluid. While recreation and leisure-based motivation and behaviors are evident in religious tourism, this volume reiterates its rootedness in tenets from religious traditions and pilgrimages. Using fresh perspectives on place-stories, rituals, performances, that are central to pilgrimage and sacred sites, essays in this volume explain contemporary expressions of religious tourism and illustrate the dynamic nature of religious tourism as an ecosystem embedded in religious practices, rituals and performances. The explanations will benefit researchers and practioners alike and they can find numerous examples that show the significance of religious tourism for sustainable development of destinations.